2023
DOI: 10.3389/fped.2023.1062251
|View full text |Cite
|
Sign up to set email alerts
|

Timely initiation of complementary feeding practices and associated factors among children aged 6–23 months in Dessie Zuria District, Northeast Ethiopia: a community-based cross-sectional study

Abstract: IntroductionEthiopia has one of the highest infant and child mortality rates in the world. Starting from the age of 6 months, breast milk alone is not sufficient to cover all nutritional requirements. Infants and young children are at an increased risk of undernutrition. Complementary feeding must, therefore, begin at the age of 6 months. Infant and young child nutrition is a critical factor in human health, nutrition, survival, growth, and development. Therefore, the aim of this study is to evaluate the timel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Meanwhile, this report has been on the situation in sub-Sahara Africa, which was eventually worsened by the COVID-19 pandemic. Mohammed et al, [26] showed that the timely initiation of complementary feeding was 83% in Ethiopia, later recorded as 52% by Abate et al [27]. This scenario was also the same in Nigeria. In Ogun State of Nigeria, Ogunlesi et al [28] reported that 41% of mothers had timely initiation of complementary feeding practices, which was later reported by Anaemene & Sogunle [29] to be 11.8%.…”
Section: Discussionmentioning
confidence: 87%
“…Meanwhile, this report has been on the situation in sub-Sahara Africa, which was eventually worsened by the COVID-19 pandemic. Mohammed et al, [26] showed that the timely initiation of complementary feeding was 83% in Ethiopia, later recorded as 52% by Abate et al [27]. This scenario was also the same in Nigeria. In Ogun State of Nigeria, Ogunlesi et al [28] reported that 41% of mothers had timely initiation of complementary feeding practices, which was later reported by Anaemene & Sogunle [29] to be 11.8%.…”
Section: Discussionmentioning
confidence: 87%
“…During the fourth month of life, the infant's renal and gastrointestinal systems reach physiological maturation, enabling them to process non-milk alimentary substances [142]. Upon reaching the sixth month, the nutritional and energetic benefits procured solely from breast milk become insufficient to meet the growing metabolic demands of the infant [143].…”
Section: Introduction Of Complementary Foodsmentioning
confidence: 99%
“…Upon reaching the sixth month, the nutritional and energetic benefits procured solely from breast milk become insufficient to meet the growing metabolic demands of the infant [143]. Thus, the inclusion of complementary food is needed for the appropriate somatic and neurodevelopmental trajectory [142,144].…”
Section: Introduction Of Complementary Foodsmentioning
confidence: 99%
“…34 Children aged 6−24 months who obtain appropriate complementary nutrition also have a chance to grow and are protected from stunting. 35 The WHO advocates dietary diversity in addition to proper hygiene measures; therefore, a variety of basic food categories should be provided as part of complementary feedings to ensure a diverse nutritional intake that fulfills the developing infant's need for all nutrients. 1 The Ethiopian government has incorporated various nutrition-related strategies into its development plans and emphasizes the importance of nutrition for achieving sustainable development, for instance in the Seqota Declaration, which aims to eradicate child malnutrition by the year 2030.…”
Section: Introductionmentioning
confidence: 99%
“… 34 Children aged 6−24 months who obtain appropriate complementary nutrition also have a chance to grow and are protected from stunting. 35 …”
Section: Introductionmentioning
confidence: 99%